Analisis Yuridis Penegakan Hukum terhadap Pelaku Penganiayaan Studi Kasus Mario Dandy - Saher Remal Agungta Ketaren; Fadzal Mutaqin; Jennifer Natalia Abigael L Tobing; Yaumil Azza; Alya Sofiatuzzahra Achriansyah; Felicia Stefanie Setiawan; Ahda Fadhila Putri; Mulyadi M (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Law enforcement is an effort so that legal norms in society can run according to their purposes. In upholding justice, law enforcement officers are expected to be able to carry out their obligations to uphold the law against perpetrators, especially perpetrators of abuse. The problems in this journal are: First, how is the law enforcement against the perpetrators of abuse. Second, how did the public react to the abuse case by Mario Dandy. The research method that the author uses is a normative research method with data collection procedures sourced from legal materials containing various normative legal rules. The data that the authors obtain and process are secondary data derived from library sources. The author sources the literature by studying literatures, articles, and internet sites related to this research. The results showed that the perpetrators of the persecution, in this case Mario Dandy, were charged with Article 355 paragraph (1) of the Criminal Code subsidiary 354 paragraph (1) of the Criminal Code of the subsidiary 353 paragraph (2) of the Criminal Code of the subsidiary 351 paragraph (2) of the Criminal Code and/or 76 C juncto 80 Child Protection Law. This is what makes him threatened with imprisonment for a maximum of 12 years. So based on the law enforcement, the public reaction was generated which was very angry to Mario Dandy and hoped that this case would be legally processed quickly and would not end peacefully so that this incident could be a lesson for teenagers and parents in educating and paying attention to their children's behavior. Therefore, law enforcement is needed that is able to provide truth and justice by legal officials, so that people can be more careful in their actions and teach their children a lesson.